Development of a Banana Peel Waste-Based Bio-Battery as a Learning Media on Voltaic Cell Material - Tiara Tiara; Raudhatul Fadilah; Fitriani Fitriani (Postgraduate, University of Mataram, 2025)
This study aims to develop an experimental-based learning media in the form of a biobattery made from banana peel waste for the topic of voltaic cells. The research method used is the ADDIE development model. The analysis stage was carried out through curriculum review, observation of student needs, and identification of banana peels as a potential electrolyte material. In the design stage, a worksheet was prepared that was integrated with the procedure for making a simple biobattery. The development process included fabricating a biobattery from banana peels, assembling a simple voltaic cell, and creating an interactive learning media. Validation was carried out by material experts and media experts, resulting in an average feasibility score of 0.91 and 0.93, respectively, which are categorized as high. Practicality was assessed through a questionnaire, with small group trials achieving a score of 73.96% (practical) and field trials reaching 94.89% (very practical). Limited trials involving students in grades XI and XII showed that this media not only improved conceptual understanding of voltaic cells but also fostered environmental awareness through the utilization of organic waste. The evaluation results indicate that the biobattery learning media is suitable for use as an alternative tool for contextual and environmentally friendly chemistry practicums.